To get the second partial derivatives, we must determine the f1st partial derivative of the given function.
We'll differentiate with respect to x: dz/dx.
z=x^2*y + 2x*e^1/y
We'll differentiate the expression of z with respect to x, treating y as a constant.
dz/dx = (d/dx)(x^2*y + 2x*e^1/y)
dz/dx = y(d/dx)(x^2) + (2e^1/y)(d/dx)(x)
The first partial derivative, with respect to x, is:
dz/dx = 2xy + 2e^1/y
d^2z/dx*dy= x^2 - 2xe^1/y/y^2
To calculate the first partial derivative of z, with respect to y, we'll have:
dz/dy = (d/dy)(x^2*y + 2x*e^1/y)
dz/dy = x^2 - 2xe^1/y/y^2
d^2z/dy*dx = 2x - 2e^1/y/y^2